2006
DOI: 10.1289/ehp.8143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organochlorine Contaminants on Loggerhead Sea Turtle Immunity: Comparison of a Correlative Field Study andIn VitroExposure Experiments

Abstract: Several laboratory and field studies indicate that organochlorine contaminants (OCs), such as poly-chlorinated biphenyls (PCBs) and pesticides, modulate immune responses in rodents, wildlife, and humans. In the present study we examined the effects of OCs on immunity in free-ranging loggerhead sea turtles (Caretta caretta). Mitogen-induced lymphocyte proliferation responses, lysozyme activity, and OC concentrations were measured from blood samples. Mitogens chosen in the lymphocyte proliferation assay were phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(97 citation statements)
references
References 42 publications
2
91
1
1
Order By: Relevance
“…Our results contrast with those of previous studies that have measured in vitro lymphocyte proliferation responses in reptiles. While studies in another snake species found higher immune responses in females (Saad and Shoukrey 1988;Saad 1989), two studies in turtles reported no sex differences (Muñoz and De la Fuente 2001b; Keller et al 2006). On the other hand, the lack of sex differences in innate immunity parallels findings in water pythons (Ujvari and Madsen 2011) and marine iguanas (French et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Our results contrast with those of previous studies that have measured in vitro lymphocyte proliferation responses in reptiles. While studies in another snake species found higher immune responses in females (Saad and Shoukrey 1988;Saad 1989), two studies in turtles reported no sex differences (Muñoz and De la Fuente 2001b; Keller et al 2006). On the other hand, the lack of sex differences in innate immunity parallels findings in water pythons (Ujvari and Madsen 2011) and marine iguanas (French et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Continuous low-level exposure to oil in the form of tar balls, slicks, or elevated background concentrations also challenge animals facing other natural and anthropogenic stresses. Types of trauma can include skin irritation, altering of the immune system, reproductive or developmental damage, and liver disease (Keller et al 2004;Keller et al 2006). Chronic exposure may not be lethal by itself, but it may impair a turtle's overall fitness so that it is less able to withstand other stressors .…”
Section: Marine Pollution and Environmental Contaminationmentioning
confidence: 99%
“…Past attention was focused on measuring body burdens of various pollutants to wild reptiles which gave an understanding of historical exposure of given populations (Buono et al, 2007;Holem et al, 2008;Mann et al, 2007;Moss et al, 2009;Trinchella et al, 2006;De Falco et al, 2007;Keller et al, 2006;Simoniello et al, 2010;van de Merwe et al, 2010). However, the population-level effects and actual risks of pollutants on reptiles are still generally understudied (Weir et al, 2010).…”
Section: Introductionmentioning
confidence: 99%